Foreign body responses in mouse central nervous system mimic natural wound responses and alter biomaterial functions - Timothy M. OʼShea (Nature Portfolio, 2020)
Implantable biomaterials evoke foreign body responses in the central nervous system. The authors compare hydrogel-based biomaterials to identify cellular interactions and molecular mechanisms that drive different types of foreign body responses that have different effects on biomaterial function.